2016
DOI: 10.1007/s00784-016-1784-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different collagen modifications for titanium and titanium nitrite surfaces on functions of gingival fibroblasts

Abstract: Our results demonstrate a simple, yet effective, method for collagen coating on titanium implants to improve the long term integration and stability of dental implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Implant materials with an antimicrobial interface promote the growth and proliferation of cells and inhibit the adhesion and expansion of bacteria [22]. Cell adhesion and a cellbiomaterial interface are complicated processes associated with a number of factors [23,24] such as cell biological behaviors and material surface properties as well as environmental factors including hydrophilicity, charge, roughness, hardness, and chemical composition [25]. For example, material surface roughness affects cell spreading.…”
Section: Discussionmentioning
confidence: 99%
“…Implant materials with an antimicrobial interface promote the growth and proliferation of cells and inhibit the adhesion and expansion of bacteria [22]. Cell adhesion and a cellbiomaterial interface are complicated processes associated with a number of factors [23,24] such as cell biological behaviors and material surface properties as well as environmental factors including hydrophilicity, charge, roughness, hardness, and chemical composition [25]. For example, material surface roughness affects cell spreading.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, titanium dioxide nanoparticles synthesized as nanoneedles, titanate scrolled nanosheets, and gel-sol-based isotropic nanoparticle aff ect intracellular calcium homeostasis, thereby leading to endoplasmic reticulum stressdependent toxicity (Simon et al 2017). However, the genotoxicity of titanium nitride nanoparticles, which have favorable properties and are used for coronary stents, syringe needles, and the coating of orthopedic implant as well as in dental medicine for improving long-term implants (van Hove et al 2015;Chu et al 2016;Karjalainen and Nammas 2016;Ritz et al 2016), has not been studied yet. Very little is known about the toxicity of chromium containing nanoparticles (Alarifi et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…about the toxicity, including genotoxicity, induced by these nanoparticles (van Hove et al 2015;Chu et al 2016;Karjalainen and Nammas 2016;Ritz et al 2016). At the same time, for ultrafi ne titanium dioxide nanoparticles, which are widely used in the number of applications, including white pigment in paint, ceramics, food packaging materials, food additives, cosmetic creams, toothpastes, and components of surgical implants, it has been shown that the longterm exposure to titanium dioxide nanoparticles led to their accumulation in brain, oxidative stress, overproliferation of all glial cells, tissue necrosis as well as hippocampal cell apoptosis, which resulted in neurogenic disease states in mice (Ze et al 2014;Rollerova et al 2015).…”
mentioning
confidence: 99%
“…Furthermore, recently was shown that oral administration of titanium dioxide nanoparticles disrupts hepatic metabolic functions in a mouse model [3]. Titanium nitride nanoparticles have favorable proper ties and are used for the coating of orthopedic implant, coronary stents, and syringe needles as well as for improving long-term implants in dental medicine [4][5][6][7]. At the same time, very little is known about the toxicity including genotoxicity induced by titanium nitride nanoparticles and the effect of these nanoparticles on liver gene expressed profile has not been reported.…”
Section: We Have Studied the Effect Of Chromium Disilicide And Titanimentioning
confidence: 99%
“…For titanium dioxide nanoparticles, which are widely used in the number of applications, including cosmetic creams, toothpastes, and component of surgical implants, it was shown that long-term exposure to these nanoparticles led to accumulation of these nanoparticles in brain, over-proliferation of glial cells and significant changes in brain gene expressions as well as to neurogenic disease states in mice [1,2]. At the same time, the genotoxicity of titanium nitride nanoparticles, which have favorable properties and used for coronary stents, syringe needles, and the coating of orthopedic implant as well as in dental medicine for improving long-term implants [4][5][6][7], did not studied yet. At the same time, very little is known about the toxicity of chromium containing nanoparticles [8].…”
Section: Fig 3 Effect Of Prolonged Treatment Of Mice (2 Months) By mentioning
confidence: 99%